2022
DOI: 10.2105/ajph.2017.304247
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Outcomes of Women Who Receive and Women Who Are Denied Wanted Abortions in the United States

Abstract: Women denied an abortion were more likely than were women who received an abortion to experience economic hardship and insecurity lasting years. Laws that restrict access to abortion may result in worsened economic outcomes for women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
124
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(132 citation statements)
references
References 18 publications
2
124
0
Order By: Relevance
“…The belief expressed by some students that having a child would not change their career goals is inconsistent with findings that women who carry unwanted pregnancies to term are less likely than women who terminate unwanted pregnancies to have and achieve aspirational one‐year plans . However, most female students were very concerned about the impact of childbearing on career goals or poverty, which echoes findings in the literature that unintended childbearing reduces full‐time employment and increases poverty and public assistance …”
Section: Discussionmentioning
confidence: 75%
“…The belief expressed by some students that having a child would not change their career goals is inconsistent with findings that women who carry unwanted pregnancies to term are less likely than women who terminate unwanted pregnancies to have and achieve aspirational one‐year plans . However, most female students were very concerned about the impact of childbearing on career goals or poverty, which echoes findings in the literature that unintended childbearing reduces full‐time employment and increases poverty and public assistance …”
Section: Discussionmentioning
confidence: 75%
“…Longitudinal research among U.S. women who were unable to obtain wanted abortions found that, compared with individuals who had terminated a pregnancy, those who had been denied an abortion and forced to carry to term experienced more debt, had lower credit scores 18 and were more likely to have poverty-level incomes four or more years later. 19 They also experienced more chronic pain, had worse self-reported health 20 and were more likely to experience sustained physical violence from the man involved in the pregnancy. 21 The rights and health of all pregnant individuals are compromised by policies that ban or limit access to abortion under the guise of a public health response to COVID-19.…”
Section: Potential Consequences For Individualsmentioning
confidence: 99%
“…There is a substantial and growing body of literature examining impacts of extant restrictive abortion policies and women's experiences of these policies Previous research indicates some restrictive abortion policies-such as gestational limits, laws requiring abortion providers to have hospital admitting privileges (and which can lead abortion clinics to close), lack of Medicaid funding to pay for low-income women's abortions, and multiple policies in combination-put abortion out of reach for some women [5][6][7][8][9]. There is also a robust body of research that documents adverse impacts on women and children when women are unable to obtain wanted abortions; these include: economic insecurity, adverse physical health impacts, ongoing violence from the man involved in the pregnancy, and adverse impacts on children's development and maternal bonding [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%